Social policy review. edited by Nick Ellison, Linda Bauld and Martin Powell. - Ellison, Nicholas, 1952-; Bauld, Linda; Powell, Martin (The Policy Press, 2004)
Social Policy Review 16 is an excellent source of information and opinion about core aspects of contemporary social policy for students and academics alike. It will also appeal to all those with an interest in 'welfare' in the widest sense of the term.